Relation of coagulation factor XI with incident coronary heart disease and stroke: the Cardiovascular Health Study. - Appiah, Duke; Fashanu, Oluwaseun E; Heckbert, Susa R; Cushman, Mary; Psaty, Bruce M; Folsom, Aaron R (Blood Coagul Fibrinolysis, 2016)
The role of coagulation factor XI (FXI) in the cause of arterial thrombotic events remains uncertain. We examined the association of FXI with incident coronary heart disease (CHD), ischemic stroke, and hemorrhagic stroke. Data were from 3394 adults (mean age: 74.5 years) enrolled in the Cardiovascular Health Study who had FXI antigen from plasma samples drawn in 1992-1993 and were followed for cardiovascular events until 30 June 2013. Approximately 63% of participants were women and 17% were black. FXI levels were higher in blacks and women, showed positive associations with high-density lipoprotein and total cholesterol, BMI and diabetes, and negative associations with age and alcohol intake. During median follow-up of 13 years, we identified 1232 incident CHD, 473 ischemic stroke, and 84 hemorrhagic stroke events. In multivariable Cox models adjusted for traditional cardiovascular disease risk factors, the hazard ratio per one SD (32.2 mg/dl) increment of FXI was 1.02 (95% confidence interval: 0.96-1.08) for CHD; 0.94 (0.85-1.04) for ischemic stroke, and 0.85 (0.65-1.10) for hemorrhagic stroke. In this prospective cohort of elderly adults, there was no statistically significant association of higher FXI levels with incident CHD and stroke.